2019
DOI: 10.2147/ott.s210952
|View full text |Cite
|
Sign up to set email alerts
|

<p>TCF-4 Regulated lncRNA-XIST Promotes M2 Polarization Of Macrophages And Is Associated With Lung Cancer</p>

Abstract: BackgroundLittle is known about the biological function of long non-coding RNA X inactive specific transcript (lncRNA XIST) and its underlying mechanism in tumor-associated macrophage (TAM) polarization of lung cancer.Materials and methodsThe expression of lncRNA XIST in macrophages was detected by RT-qPCR. The function of lncRNA XIST on IL-4-induced M2 polarization was evaluated by transfection of shRNA and RT-qPCR or Western blotting detection of M2 specific markers. Contact between T-cell-specific transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 27 publications
0
42
0
Order By: Relevance
“…Additionally, elevated expression of CTSW is associated with favourable prognosis in patients diagnosed with endometrial cancer 139 . JPX, a long, non-coding RNA X-inactive specific transcript activator, can also be involved in M1-M2 macrophage polarization 140 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, elevated expression of CTSW is associated with favourable prognosis in patients diagnosed with endometrial cancer 139 . JPX, a long, non-coding RNA X-inactive specific transcript activator, can also be involved in M1-M2 macrophage polarization 140 .…”
Section: Discussionmentioning
confidence: 99%
“…TCF-4 can modulate lncRNA-XIST and promote M2 polarization of macrophages, thus induce lung cancer. 29 Besides, TCF-4 is observed to bind to the LINC01278 promoter and participates in hepatocellular carcinoma (HCC) metastasis. 30 In this study, TCF-4 could bind to HCP5 promoterregion and regulated HCP5 expression in IHH-4 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies had demonstrated that lncRNA NIFK-AS1 and lncRNA CCAT1 could inhibit the polarization of M2 macrophages by targeting miR146a and miR-148a, respectively [50,51]. Moreover, lncRNA XIST and lncRNA GNAS-AS1 exhibited the promotion of M2 polarization, such functions were associated with T-cellspecific transcription factor 4 (TCF-4) and miR-4319, respectively [52,53].…”
Section: Lncrnas Regulate Macrophage Infiltration Polarization and mentioning
confidence: 99%